Ta'tsirul lahjatil mahaliyyah madinah jambi seberang 'alaas tikhdaamil lughatil 'arabiyyati fii madrasah al jauharen al islamiyyah: Pengaruh Dialek Kota Jambi (Seberang) Terhadap Penggunaan Bahasa Arab Di Madrasah Al-Jawharen Al islamiyyah - Adilla Cahyani Putri; Sulhi Muhamad Daud Abdul Kadir; Salman Jufri; Abdul Muid; Firman Afrian Pratama (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
This research aims to describe and understand how the local dialect of Jambi City (seberang) affects the use of Arabic in Al-Jawharin Islamic School. This research was conducted in Al Jawharin Islamic School from March to April 2024. Data for this research were obtained through field observation, interviews with information sources, and documents. The type of research used is qualitative research with a descriptive approach. The researcher’s data sources in this research are the school principal, Arabic language teachers, care teachers, administration members responsible for the language, and high-level students at Al Jawharana Islamic School. This effort aims to understand how the Jambi Seberang dialect is used and formed in classical Arabic for the students of Al-Jawharana School. Islamic. The results of this study include several factors, 1) influenced by the mother tongue intervention. What is meant by mother tongue is the first language that a child receives in his environment and uses to achieve communication between him and those around him. 2) The existence of cultural and linguistic contact between people who speak the two languages. 3) There are advantages and disadvantages to using the Seberang dialect of Jambi City over Standard Arabic for the students of Al-Jawharin School. The researcher concluded that the overlap of the dialect of the city of Jambi Seberang with classical Arabic greatly affects Arabic vocabulary. This influence reflects the dynamic relationship between the two languages and demonstrates the increasing linguistic diversity in the Jambi community. However, there must be awareness of the need to preserve the Arabic language as a valuable cultural asset and a bridge for communication with the wider Arab world.